The Effect of “Han So Hee” Brand Ambassador and E-Wom on Customer Loyalty with Purchase Decision as an Intervening Variable (Study on Consumers of Beauty Products Somethinc) - Iklila Amiroh; Sudarmiatin Sudarmiatin; Agung Winarno (Citakonsultindo, 2023)
The purpose of this study was to determine the effect of Brand Ambassador, E-Wom on Customer loyalty through Purchase Decisions for consumers of Somethinc beauty products who make purchases using online marketplaces. This research is quantitative research using SEM-PLS. Survey data was collected online and found 246 respondents. Brand Ambassador and E-Wom have a positive and significant effect on the Purchase Decision, H1 and H2 are accepted. Brand Ambassador, E-Wom and Purchase Decision have a positive and significant direct effect on Customer loyalty, H3, H4, and H5 are accepted. Meanwhile, Purchase Decision has a positive and significant effect mediating Brand Ambassador and E-Wom on Customer loyalty, H6, and H7 as mediating variables are accepted. Theoretical implications in this study can contribute to the study of digital marketing literacy